Identification of an Escherichia coli Operon Required for Formation of the O-Antigen Capsule - Peleg, Adi (American Society for Microbiology, 2005)
Escherichia coli produces polysaccharide capsules that, based on their mechanisms of synthesis and assembly, have been classified into four groups. The group 4 capsule (G4C) polysaccharide is frequently identical to that of the cognate lipopolysaccharide O side chain and has, therefore, also been termed the O-antigen capsule. The genes involved in the assembly of the group 1, 2, and 3 capsules have been described, but those required for G4C assembly remained obscure. We found that enteropathogenic E. coli (EPEC) produces G4C, and we identified an operon containing seven genes, ymcD, ymcC, ymcB, ymcA, yccZ, etp, and etk, which are required for formation of the capsule. The encoded proteins appear to constitute a polysaccharide secretion system. The G4C operon is absent from the genomes of enteroaggregative E. coli and uropathogenic E. coli. E. coli K-12 contains the G4C operon but does not express it, because of the presence of IS1 at its promoter region. In contrast, EPEC, enterohemorrhagic E. coli, and Shigella species possess an intact G4C operon.